2014
DOI: 10.1002/2014jc009970
|View full text |Cite
|
Sign up to set email alerts
|

Ocean subsurface studies with the CALIPSO spaceborne lidar

Abstract: The primary objective of the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) mission is to study the climate impact of clouds and aerosols in the atmosphere. However, recent studies have demonstrated that CALIPSO also collects information about the ocean subsurface. The objective of this study is to estimate the ocean subsurface backscatter from CALIPSO lidar measurements. The effects of the lidar receiver's transient response on the attenuated backscatter were first removed in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 32 publications
0
75
0
1
Order By: Relevance
“…Behrenfeld et al (2013) used CALIOP measurements to quantify global ocean phytoplankton biomass and total particulate organic carbon stocks. Lu et al (2014) found significant relationships between integrated subsurface backscatter and chlorophyll-a concentration, as well as particulate organic carbon, which indicate a potential use of the CALIPSO lidar to estimate global chlorophyll-a and particulate organic carbon concentrations. Lu et al (2016) introduced an approach to estimate the ocean subsurface layer-integrated backscatter and particulate backscattering coefficient from CALIOP 30 • off-nadir lidar measurements.…”
Section: Spaceborne Lidarmentioning
confidence: 84%
“…Behrenfeld et al (2013) used CALIOP measurements to quantify global ocean phytoplankton biomass and total particulate organic carbon stocks. Lu et al (2014) found significant relationships between integrated subsurface backscatter and chlorophyll-a concentration, as well as particulate organic carbon, which indicate a potential use of the CALIPSO lidar to estimate global chlorophyll-a and particulate organic carbon concentrations. Lu et al (2016) introduced an approach to estimate the ocean subsurface layer-integrated backscatter and particulate backscattering coefficient from CALIOP 30 • off-nadir lidar measurements.…”
Section: Spaceborne Lidarmentioning
confidence: 84%
“…Preliminary investigations have demonstrated that data from an existing aerosol lidar on the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) satellite can detect sub-surface oceanic scattering [49][50][51]. This system, designed for atmospheric measurements, does not have sufficient range resolution for detailed profiles of oceanic backscatter, but airborne measurements have demonstrated that a future orbiting lidar designed for both atmospheric and oceanic profiling could provide valuable information.…”
Section: Discussionmentioning
confidence: 99%
“…With that goal in mind, a monthly global dataset of daytime and nighttime aerosol extinction profile is available and known as Level3 aerosol product (Winker et al, 2013). Various research fields such as monitoring of stratospheric aerosol and aerosol distribution (Thomason et al, 2007), estimating the ocean subsurface (Lu et al, 2014), documenting shallow subsurface oil (Leifer et al, 2012), global distributing of the clear-sky occurrence rate during the daytime (Eguchi and Yokota, 2008), and dust detection (Luo et al, 2015;Brakhasi et al, 2018) have been studied using CALIPSO LIDAR observations. The various products of CALIOP and their corresponding product level are given in table 2.…”
Section: Calipso Satellitementioning
confidence: 99%